Bilateral Optic Disc Drusen in Hypermetropic Children of a Family - Syeda Aisha Bokhari, Ghulam Mustafa Memon, Shakir Zafar, Munira Shakir, Zeeshan Kamil (Pakistan Journal of Ophthalmology, 2012)
Optic disc drusen are calcified, round, yellow nodules, with various sizes tend to be located within any part of the optic nerve head. According to most theories they are caused by impaired ganglion cell axonal transport, probably related to a small sclera canal and mechanical obstruction. We report a case of 12 year old male child and his 13 year old sister, both presented with decrease vision in our outpatient department. Fundus examination of both patients revealed bilateral optic disc swellings with no hyperemia. After investigations, it was proved that both patients suffered from bilateral buried optic